2016
DOI: 10.1136/thoraxjnl-2015-208273
|View full text |Cite
|
Sign up to set email alerts
|

Physical rehabilitation interventions for adult patients during critical illness: an overview of systematic reviews

Abstract: BackgroundPhysical rehabilitation interventions aim to ameliorate the effects of critical illness-associated muscle dysfunction in survivors. We conducted an overview of systematic reviews (SR) evaluating the effect of these interventions across the continuum of recovery.MethodsSix electronic databases (Cochrane Library, CENTRAL, DARE, Medline, Embase, and Cinahl) were searched. Two review authors independently screened articles for eligibility and conducted data extraction and quality appraisal. Reporting qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
75
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 39 publications
0
75
0
8
Order By: Relevance
“…Adjunctive technologies including electrical muscle stimulation and cycle ergometry may also be employed. The safety and feasibility of early mobilization have been well documented, and its efficacy has been examined in a number of systematic reviews demonstrating significant benefit in health‐related quality of life, physical function, respiratory and peripheral skeletal muscle strength, length of ICU and hospital stay, and duration of mechanical ventilation . However, the post‐ICU discharge stages of recovery have been relatively under‐examined, and given the residual impairments in physical function evident in ICU survivors, there is rationale for the ongoing delivery of exercise‐based rehabilitation interventions …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adjunctive technologies including electrical muscle stimulation and cycle ergometry may also be employed. The safety and feasibility of early mobilization have been well documented, and its efficacy has been examined in a number of systematic reviews demonstrating significant benefit in health‐related quality of life, physical function, respiratory and peripheral skeletal muscle strength, length of ICU and hospital stay, and duration of mechanical ventilation . However, the post‐ICU discharge stages of recovery have been relatively under‐examined, and given the residual impairments in physical function evident in ICU survivors, there is rationale for the ongoing delivery of exercise‐based rehabilitation interventions …”
Section: Introductionmentioning
confidence: 99%
“…The safety and feasibility of early mobilization have been well documented, [24][25][26][27][28] and its efficacy has been examined in a number of systematic reviews demonstrating significant benefit in health-related quality of life, physical function, respiratory and peripheral skeletal muscle strength, length of ICU and hospital stay, and duration of mechanical ventilation. [29][30][31][32] However, the post-ICU discharge stages of recovery have been relatively under-examined, and given the residual impairments in physical function evident in ICU survivors, there is rationale for the ongoing delivery of exercise-based rehabilitation interventions. 30 This paper provides an executive summary of a recent Cochrane Collaboration systematic review, 33 which synthesizes evidence for exercise-based rehabilitation initiated after ICU discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that rehabilitation in this population is safe and feasible, involving respiratory muscle strength, limb and arm muscles strength, activities of daily living (ADL) functional scores and effort tolerance [5][6][7][8]. Two recent reviews by Elliot et al [9] and Connolly et al [10] describe a high variability in muscle strength evaluations, functional activity tests, walking assessments, and patient-centered outcomes such as healthrelated quality of life in survivors of ICU. The Authors conclude that sensitivity and validity of measures in survivors of a critical illness have not yet been established and new tools need to be developed to appropriately assess the weakness and poor physical function in order to measure effectiveness of interventions [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent reviews by Elliot et al [9] and Connolly et al [10] describe a high variability in muscle strength evaluations, functional activity tests, walking assessments, and patient-centered outcomes such as healthrelated quality of life in survivors of ICU. The Authors conclude that sensitivity and validity of measures in survivors of a critical illness have not yet been established and new tools need to be developed to appropriately assess the weakness and poor physical function in order to measure effectiveness of interventions [9,10]. In fact, the majority of studies carried out take into consideration only some aspects of patient's disability, but no study has performed a comprehensive and objective rehabilitative assessment with the most common measures used in this field to detect their feasibility.…”
Section: Introductionmentioning
confidence: 99%